Load-flow and Stable Planning of Radial Distribution Networks using Distributed Generation - Bhullar, Suman (My University, 2019)
The distribution networks execute perceptible evolution due to the wide range of load levels in daily routine as compared to transmission networks. In this thesis, it has been tried to discover the possibilities associated with the efficient operation of electric power distribution networks. A systematic load- flow is necessary for proper working as well as control, well- organized planning and cost effective optimization of distribution networks. The objective of this research work is to develop simple and efficient load-flow solution for radial distribution networks assumed to be of balanced nature, which is providing platform for the mechanism involved in the stable planning of distribution networks using distributed generation. In this work, an array based novel searching technique is used to solve the load-flow of radial distribution networks in an iterative method. The proposed technique is used to identify the nodes beyond the branch and hence helpful in calculation of node current and then branch current. Simple equations are used to relate the sending-end voltage, receiving-end voltage and voltage drops in each branch of the distribution system. A computer algorithm is developed to find out the respective parameters considering flat voltage profile by using backward/forward sweep. The angle of the receiving-end voltage is also computed along with the magnitude of the voltage. The comparison of proposed method with the other available methods reported in the literature has been verified on seven radial distribution networks including one practical Indian feeder to show its efficiency. DG technologies developed for the distribution systems, which comprise of conservative as well as non-conservative types of energy sources for the generating power, are procuring thrust and playing leading role in the distribution system by providing substitute for distribution system planning option. The optimal allocation of DG in any distribution network reduces the loss of the system and increases the voltage profile and hence stability of the system. In power distribution network, losses occurring in the network are one of the important components, and effort should be done to reduce their value. In this work, hybrid Artificial Bee Colony and Cuckoo Search optimization technique is utilized for siting and sizing of DG for loss reduction. Instead of integrating a single large size DG, two or more than two small DGs (multi DGs) are usually placed. These DGs must be placed in appropriate buses/nodes with suitable size to ensure better performance of the system. The multi DGs are optimally placed by considering objectives like power loss, penalty function (PE) and voltage profile (VP). The outcomes of two different types of radial distribution networks obtained by the suggested method for placement of multi DGs have been correlated to that obtained by using other optimization techniques. The proposed method has also been correlated with the other published methods to indicate its strength. Whenever there is increase in load demand, the chances are more for voltage instability. In this work, an attempt has been made to propose a new suitable voltage stability index (VSI) for radial distribution networks. The VSIs available in literature are based on reduction of network and without considering the voltage angle. The proposed VSI has been derived without reduction of the network and without neglecting voltage angle. In the present work total seven different types radial distribution networks (RDNs) have been considered including one practical RDN. The results obtained by the proposed method have been compared with that of obtained by the other available methods. An effective planned distribution network not only reduces the loss of the system, but also enhances the voltage profile and stability of the system. In this work, a technique is suggested for optimal planning of distribution networks using DG. The optimal location of the substation is found by genetic algorithm incorporating the proposed “voltage stability index” as the objective function. The node points are connected to the substation in optimum routes in such a way that the network becomes radial. The outcomes of the proposed planned network for single feeder case, double feeder case and triple feeder case have been compared with an existing planning system keeping the system data unaltered. The three feeder configuration suits to the utility. Next the three DG units are integrated to this network for three feeder case.
Ph.D. Thesis
Keywords: Load-flow; VSI; DG; Substation; Planning; ABC-CS; GA